2021
DOI: 10.1038/s41598-021-98538-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of thalidomide in an experimental brain death liver donor model

Abstract: Brain death is characterized by a generalized inflammatory response that results in multiorgan damage. This process is mainly mediated through cytokines, which amplify graft immunogenicity. We investigated the immunological response in a brain death liver donor model and analysed the effects of thalidomide, a drug with powerful immunomodulatory properties. Brain death was induced in male Lewis rats. We studied three groups: Control (sham-operated rats in which trepanation was performed without inserting the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…We also observed that the levels of IL-1β were greater in the BD and TLD groups than in the CTR group and greater in the BD group than in the TLD group, reinforcing the hypothesis that BD generates an inflammatory process and the effective action of thalidomide on this marker. These results are in agreement with findings in the literature and in previous studies by our group with samples of liver and kidney tissue 23 – 25 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We also observed that the levels of IL-1β were greater in the BD and TLD groups than in the CTR group and greater in the BD group than in the TLD group, reinforcing the hypothesis that BD generates an inflammatory process and the effective action of thalidomide on this marker. These results are in agreement with findings in the literature and in previous studies by our group with samples of liver and kidney tissue 23 – 25 .…”
Section: Discussionsupporting
confidence: 94%
“…According to immunohistochemical analysis, BD increased the activation of NF-ĸB through the generated inflammatory process, while thalidomide significantly reduced this activation to levels equal to those of the control group. These findings are in agreement with published studies and were also demonstrated in a previous study by our group, which confirmed the anti-inflammatory effects of thalidomide on liver tissue through a significant reduction in the number of M1 macrophages 23 . Considering the mechanism of action of thalidomide, we expected an increase in IL-10 expression and a significant decrease in IL-6 expression in the TLD group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As a first consequence, it remains unclear if the immune system is impacted by brain death and whether a deceased recipient does not precisely mirror the response of a living body to a xenograft. Robust evidence indicates an increase in systemic immune response and local inflammatory reactions in brain‐dead subjects 7 . This altered state may manifest as either an enhanced or, conversely, a diverted immune response in the context of brain death.…”
Section: The Decedent Model Of Xenotransplantationmentioning
confidence: 99%
“…This process is mainly mediated through cytokines, which amplify graft immunogenicity. (3) Common side effects include constipation, hypothyroidism, ACTH stimulation, hypoglycemia, xerostomia, fever, mood changes,, peripheral neuropathy, somnolence, sedation, rash, and deep vein thrombosis (4) Though the use of Thalidomide was banned in most countries at that time, it proved to be a useful treatment for leprosy and later, multiple myeloma. (5) Thalidomide increases the risk of deep vein thrombosis (DVT) and pulmonary embolism (PE) in patients receiving treatment for multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%